Technology and architecture: Impact of artificial intelligence and virtual reality on the perception of architectural design - Cañari Rodriguez, Jhanella Katheryn (2025)
The search for innovation in architecture with new technologies focuses on the convergence between artificial intelligence (AI) and virtual reality (VR) in the field of architectural design, taking into account the perception and sensation of virtual spaces i n the shot of architects' decisions in the design process. The study aims to evaluate the level of perception, realism and sensation experienced by sensory characters immersed in architectural virtual spaces designed through comparative technological combi nation in a 2D environment. An experimental methodology was used based on a diagnosis according to the principles of neuroarchitecture, identifying the considerations related to sensory characters, followed by the grammatical generation of the prompt to obtain 2D images through AI, which were recreated in 3D models through of the Oculus Quest 2. Specific questions were raised that examine the sensations, perception and realism in the spaces created by Artificial Intelligence, collaborating with the virtual virtualization platform. The comparative analysis between the sensations anticipated by the designer, those experienced in the virtual space and the 2D visualization had a favorable impact on the perception and sensation of the virtual space designed using image generators. An innovative perspective for decision - making in architectural design is proposed, concluding that the integration of artificial intelligence image generators with VR suggests significant potential for the application of this technological synergy in the architectural field, which provides new opportunities for the practical application of these technologies in the workplace. These conclusions contri bute to the understanding of how these technologies can be used in the design process to improve the quality of architectural spaces and educate future architects in new technologies.